The power of reality, in Zubiri, Sofocles and Beckett - Sanmartín Catalán, Carlos; Herreras Maldonado, Enrique (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This work aims to explain the concept «power of reality» in the philosophy of Xavier Zubiri. Being this its core, we wanted to face its reflection with other authors related to an artisticphilosophic context. Authors in which, like the spanish philosopher, is the power of the real, of the real particular things, what provides the axis of their works. Men reaches, through this power, its funcionality regarding the rest of real things, included human being. In the first place, we will introduce ourselves in the wide reflextion of Zubiri, related to two complex concepts, that one of «power», and that one of «real». Then we will introduce in the tragic sight, with special consideration on King Edipus, by Sofocles, a work that allows to see how that power is produced from the experience of tragic experience, which helps us to understand the perspective of Zubiri, who also emphasizes the meaning of tragic reality. Adding the writer Samuel Beckett is made herebecause his work, specialy Waiting for Godot, can make a contrast for us, and a challenge at the same time, for the zubirian sight, from a philosophical perspective of the absurd.